PTH(1‐84) Administration in Hypoparathyroidism Transiently Reduces Bone Matrix Mineralization. (28th July 2015) - Misof, Barbara M; Roschger, Paul; Dempster, David W; Zhou, Hua; Bilezikian, John P; Klaushofer, Klaus; Rubin, Mishaela R
ABSTRACT: Patients with hypoparathyroidism have low circulating parathyroid (PTH) levels and higher cancellous bone volume and trabecular thickness. Treatment with PTH(1‐84) was shown to increase abnormally low bone remodeling dynamics. In this work, we studied the effect of 1‐year or 2‐year PTH(1‐84) treatment on cancellous and cortical bone mineralization density distribution (Cn.BMDD and Ct.BMDD) based on quantitative backscattered electron imaging (qBEI) in paired transiliac bone biopsy samples. The study cohort comprised 30 adult hypoparathyroid patients (14 treated for 1 year; 16 treated for 2 years). At baseline, Cn.BMDD was shifted to higher mineralization densities in both treatment groups (average degree of mineralization Cn.CaMean +3.9% and +2.7%, p  < 0.001) compared to reference BMDD. After 1‐year PTH(1‐84), Cn.CaMean was significantly lower than that at baseline (–6.3%, p  < 0.001), whereas in the 2‐year PTH(1‐84) group Cn.CaMean did not differ from baseline. Significant changes of Ct.BMDD were observed in the 1‐year treatment group only. The change in histomorphometric bone formation (mineralizing surface) was predictive for Cn.BMDD outcomes in the 1‐year PTH(1‐84) group, but not in the 2‐year PTH(1‐84) group. Our findings suggest higher baseline bone matrix mineralization consistent with the decreased bone turnover in hypoparathyroidism. PTH(1‐84) treatment caused differential effects dependent on treatment duration that were consistent with the histomorphometric bone formation outcomes. The greater increase in bone formation during the first year of treatment was associated with a decrease in bone matrix mineralization, suggesting that PTH(1‐84) exposure to the hypoparathyroid skeleton has the greatest effects on BMDD early in treatment. © 2015 American Society for Bone and Mineral Research.